EFEKTIVITAS PROGRAM ME’DASENG DI KECAMATAN TABUKAN UTARA, KABUPATEN KEPULAUAN SANGIHE - Yerry Efendi Budiman; Daud Markus Liando; Donald K. Monintja (AGRI-SOSIOEKONOMI, 2021)
This study aims to describe the effectiveness of the Me'Daseng program. Measurement of effectiveness used four elements in accordance with Budiani (2009) concept namely: the accuracy of target, socialization, objectives, and monitoring. The research was conducted in the North Tabukan Sub-district, Sangihe Islands Regency. The selection of informants was carried out purposively with a total of 12 informants. The data used are primary and secondary data. Primary data were collected by conducting interviews with informants and making direct observations. Secondary data were collected by conducting literature studies and searching online data related to the theme of this research, namely program effectiveness. The data analysis technique used descriptive qualitative data analysis techniques. The results showed that (1) the Me'Daseng program was not yet fully effective, in terms of target accuracy. The community was still less involved or served when the Me'Daseng program was implemented. (2) Socialization of the Me'Daseng program has been carried out, but it has not been very good, especially the direct socialization carried out in communities. (3) The effectiveness of the Me'Daseng program when viewed from the objectives of the Me'Daseng program and compared to the results achieved, has not been very effective. (4) The government has made efforts to make improvements in the implementation of the Me'Daseng program, as an effort to pay attention to the community receiving services from the Me'Daseng program, but the impact felt by the community is still not as expected.